Deconstructing Low Birth Weight Determinants In Largest Moslem Country - Ratri Ciptaningtyas; Catur Rosidati; Hoirun Nisa; Sari, Ratna (Public Health Study Program, Faculty of Health Science, State Islamic University (UIN) Syarif Hidayatullah Jakarta, Indonesia., 2026)
Background: Low Birth Weight (LBW), defined as infants weighing <2,500 grams, is a major indicator of maternal and infant health. Globally, LBW prevalence remains high at 14.7% (≈19.8 million births in 2020) with a slow annual decline of 0.3%. In Indonesia, LBW accounts for 39.2% of neonatal deaths, with a prevalence of 6.1% (IHS 2023), still above the RPJMN 2020–2024 target of 4%. Objective: To identify determinants of LBW in Indonesia using the 2023 Indonesia Health Survey (IHS) data. Method: A cross-sectional study using secondary IHS 2023 data was conducted. The dependent variable was LBW, while independent variables followed the WHO (2004) framework: infant factors (sex, prematurity, multiple birth), maternal factors (age, education, occupation, smoking, ANC visits, anemia, hypertension, height), and environmental factors (residence type, socioeconomic status). Analyses included descriptive statistics, chi square, and binary logistic regression. Results: Significant determinants of LBW included maternal age at delivery (AOR=1.262; p=0.009), maternal height (AOR=1.661; p=0.000), hypertension status (AOR=2.503; p=0.000), preterm birth (AOR=7.822; p=0.000), infant sex (AOR=1.376; p=0.000), and birth type (AOR=14.805; p=0.000). Birth type was identified as the strongest predictor of LBW among all determinants. Conclusion: LBW in Indonesia is multifactorial. Preventive strategies should emphasize adolescent nutrition, quality antenatal care, and monitoring of high-risk pregnancies. Keywords: LBW, IHS, Multifactor, Nutrition, Determinants